If you care I care: role of Green Human Resource Management in employees green behaviors - Wajiha Rashid; Usman Ghani; Kalimullah Khan; Muhammad Usman (Cogent Business & Management)
This purpose of this study is to examine the underline mechanism (i.e. green employee empowerment (GEE)) between the relationship of green human resource management (GHRM) and green knowledge sharing (GKS) of employees. Additionally, is to examine the moderating effect of individual green value (IGV) between the relationship of GEE and GKS behaviors. Survey method was used to collect the data from employees working in manufacturing organizations of Pakistan. The study hypotheses were test with a usable sample of 359 through SPSS 22.0 and AMOS 22.0. The findings explain that GHRM has positive influence on GEE, and GEE positively influence GKS behaviors. Further, the results confirmed that GEE mediated the relationship of GHRM and GKS behaviors. Moreover, the findings also established the moderating role of IGV between the relationship of GEE and GKS behaviors such as the relationship is strengthened at high level of IGV. Also, based on the finding, implication for theory and practice, and directions for future research are discussed.